2020
DOI: 10.3390/su12020474
|View full text |Cite
|
Sign up to set email alerts
|

Does Evil Prevail? The “Bright” and “Dark” Sides of Personality as Predictors of Adaptive Performance

Abstract: The turbulent context in which organizations operate today makes them search for adaptable workers. Previous studies have shown the predictive value of the “Big Five” personality traits on adaptive performance, but some authors suggest extending personality domain with the “dark” traits of personality, that is, Machiavellianism, narcissism, psychopathy (i.e., the “Dark Triad”), and sadism (which, along with the aforementioned traits, composes the “Dark Tetrad”). The present research investigates the incrementa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…The study was self-paced. After reading and agreeing with the informed consent, participants filled in socio-demographic information concerning the socio-cultural gender with which they identified, their age and their job experience, as previous research showed that being younger, having more experience and identifying as a woman fosters adaptive performance [29,59,60]. Then, following [6,8], we provided definitions and examples for…”
Section: Institutional Review Board Statementmentioning
confidence: 99%
“…The study was self-paced. After reading and agreeing with the informed consent, participants filled in socio-demographic information concerning the socio-cultural gender with which they identified, their age and their job experience, as previous research showed that being younger, having more experience and identifying as a woman fosters adaptive performance [29,59,60]. Then, following [6,8], we provided definitions and examples for…”
Section: Institutional Review Board Statementmentioning
confidence: 99%
“…The Dark Tetrad comprises four traits [38]: narcissism, characterized by lack of empathy, attention-seeking, and sense of entitlement; Machiavellianism, based on manipulation and self-interest; subclinical psychopathy, related to the absence of remorse, antisociality, and lack of guilt; and sadism, which is related to the enjoyment of cruelty. Previous research has found that these traits have a different relationship with the job performance dimensions [34,39]: narcissism is positively related to task, contextual and adaptive performance, Machiavellianism is positively associated with task performance, psychopathy is negatively related to task and adaptive performance, and sadism is negatively linked with task performance and positively related with counterproductive behaviors at work. Regarding the relationship with biodata, to the best of our knowledge, this is the first time that is considered together.…”
Section: Plos Onementioning
confidence: 98%
“…In the case of biodata scale, this may be due to its items measures different domains [13]. Regarding dark traits, the original version of the DTW demonstrate adequate values of test-retest reliability [41], but other studies carried out with the Spanish version narcissism report values around .60 and Machiavellianism around .75 [34,35,39]. Thus, we believe that the Machiavellianism' observed reliability may be due to sample characteristics' but for narcissism scale is related with the Spanish version of the DTW.…”
Section: Limitations and Further Researchmentioning
confidence: 98%
See 1 more Smart Citation
“…, 26]. Several studies have investigated predictors of adaptive performance, some of which include self-leadership [38], ambition [39], and several of the big 5 personality traits [40], for example.…”
Section: Organizational Adaptationmentioning
confidence: 99%